Bahan Ajar Kajian Puisi Berbasis Kearifan Lokal (Piil Pesenggiri) Dengan Dukungan Media Interaktif Prezi Presentation - Dewi Ratnaningsih; Nur Mei Ningsih (Universitas Muhammadiyah Kotabumi, 2019)
The legal basis for the application of learning based on local wisdom in higher education in Indonesia is contained in Permenristekdikti Number 44 of 2015concerning the National Standards of Higher Education (SNPT). This is the basis of this research article. This study is entitled